Quantifying the Local and Spatial Effects of Alcohol Outlets on Crime - Wheeler, Andrew P. (Crime & delinquency, 2019)
This article estimates the relationship between alcohol outlets and crime at micro place street units in Washington, D.C. The analysis tests several spatial hypotheses on the local and spatial diffusion effects of on-premise and off-premise alcohol outlets on crime motivated by routine activities theory as well as theories that emphasize individual alcohol consumption. Findings show that the spatial diffusion effects of alcohol outlets are larger than the local effects, the effects of on-premise and off-premise outlets are similar in magnitude, and alcohol outlets have larger effects on interpersonal crimes than burglary. These findings are interpreted as favoring routine activities theories for why alcohol outlets increase crime, as opposed to prior research which emphasizes individual alcohol consumption.